THE COMPETENCE OF ISLAMIC EDUCATION TEACHERS IN REALISING INCLUSIVE ISLAMIC EDUCATION BASED ON GENDER EQUALITY - Rahmadani Akbar; Dwi Ratnasari (SOSIOEDUKASI, 2026)
The issue of gender inequality in Islamic education practices is still found in various aspects of learning, both in terms of curriculum, teacher attitudes and teaching materials that are still gender biased. In fact, Islam teaches the principles of justice and equality which should be reflected in the education system. This study aims to examine the competence of Islamic Religious Education teachers in realising inclusive Islamic education based on gender equality. This study uses a qualitative approach through a literature review of relevant theories and literature. The results of the study show that PAI teachers need to have pedagogical, professional, social and personal, and transformational competencies to create gender-fair and contextual learning. The conclusion of this study emphasises that the role of teachers is very strategic in shaping Islamic education that is fair and free from patriarchal bias. This study recommends teacher training and strengthening gender-sensitive curricula as concrete steps forward.